Efektivitas Konseling Kelompok Pendekatan REBT dengan Teknik Disputing Terhadap Prokrastinasi Akademik Siswa Kelas XI SMA Katolik Hikmah Mandala (International Forum of Researchers and Lecturers, 2025)
Academic procrastination is a behavior that delays completing tasks in any case so that it has a negative impact, namely that tasks are piling up and being neglected. The phenomenon found in grade XI students of Hikmah Mandala Catholic High School shows a tendency to do high procrastination, such as delaying doing tasks until the specified deadline. The REBT approach with disputing technique is used to reduce students' academic procrastination behavior by changing irrational thinking to rational. This study uses a quantitative method with a quasi-experimental design. The sample in this study was determined using the purposive sampling method and a sample of 12 students was obtained, consisting of 6 students in the experimental group and 6 students in the control group.